The SNP ratio test: pathway analysis of genome-wide association datasets - MORRIS, DEREK; HERON, ELIZABETH ANN; CORVIN, AIDEN PETER; GILL, MICHAEL; O'Dushlaine, Colm; Kenny, Elaine; Segurado, Ricardo (My University, 2009)
Summary: We present a tool that assesses the enrichment of significant associations from genome-wide association studies (GWAS) in a pathway context. The SNP ratio test (SRT) compares the proportion of significant to all SNPs within genes that are part of a pathway and computes an empirical P-value based on comparisons to ratios in datasets where the assignment of case/control status has been randomized. We applied the SRT to a Parkinson's disease GWAS dataset, using the KEGG database, revealing significance for Parkinson's disease and related pathways
PUBLISHED
Keywords: GWAS dataset; Genome-wide association studies; Parkinson's disease